La biodiversité en images - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Une image peut en dire plus long que mille mots, c’est vrai. Et quand les plus belles images du monde s’allient aux plus beaux mots, on frise la perfection.Le catalogue de Moving Pictures est la publication phare de TVE (Television Trust for...